The effect of G-CSF used after allogeneic hematopoietic stem cell transplantation on engraftment times and platelet suspension replacement numbers - Sarici, Ahmet; Erkurt, Mehmet Ali; Kuku, Irfan; Kaya, Emin; Berber, Ilhami; Bicim, Soykan; Uysal, Ayss (Pergamon-Elsevier Science Ltd, 2022)
Background: With the use of granulocyte colony stimulating factor (G-CSF) after allogeneic hematopoietic stem cell transplantation (HSCT), the duration of neutrophil engraftment and hospitalization were shortened. How-ever, there is no consensus on the effect of G-CSF on platelet engraftment time. The primary aim of our study is to determine the effect of G-CSF use on platelet engraftment time after HSCT. Secondary purposes are to determine the number of platelet suspension, number of erythrocyte suspension and incidence of acute graft versus disease after HSCT. Material and methods: Patients who had allogeneic stem cell transplantation at our center between 01.01.2011 and 01.01.2022 were retrospectively analyzed. Patients were divided into 2 groups as those who received and did not receive G-CSF after transplantation. Results: A total of 64 patients were included. While 32 patients were given post-HSCT G-CSF support, the other 32 patients were not given. Neutrophil engraftment time and length of hospital stay were shorter in the group receiving G-CSF (p < 0.05). Platelet engraftment time was shorter in the group that did not receive G-CSF (p < 0.05). The incidence of acute GVHD of the patients in group 1 tended to be higher than the patients in group 2 (40.6 % vs 15.6 %, p = 0.052). Post-HSCT platelet suspension was less in the group that did not receive G-CSF, but this difference was not statistically significant (p = 0.173). Conclusion: While the positive effect of post HSCT G-CSF use on duration of neutrophil engraftment and hospi-talization is evident, its effects on platelet engraftment need to be investigated.
Keywords: Hematopoietic stem cell transplantation; Thrombocyte engraftment time; Erythrocyte and thrombocyte replacement; number; G-CSF; Acute graft versus host disease